2015
DOI: 10.1007/s11575-015-0255-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Global Orientation on the Performance of International New Ventures: Evidence from Italy

Abstract: The aim of this paper is to investigate the relationship between global versus regional orientation and the performance of international new ventures (INVs). Building on internalization theory and organizational learning literature, we develop two competing hypotheses on the performance effect of geographic scope on INV performance. We test these hypotheses on a sample of Italian manufacturing INVs. The study extends the regionalization/globalization debate to the context of INVs. Our findings show that INVs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 107 publications
(205 reference statements)
2
45
1
Order By: Relevance
“…Moreover, the majority of companies in the current sample had a rather regional scope of activity. This finding is similar to other studies concerning the internationalising SMEs, especially those from emerging markets (Cerrato & Piva, 2015;Lopez, Kundu, & Ciravegna, 2009). Such a regional focus may be one of the typical characteristics of the accelerated expansion path followed by companies originating in the CEE countries.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the majority of companies in the current sample had a rather regional scope of activity. This finding is similar to other studies concerning the internationalising SMEs, especially those from emerging markets (Cerrato & Piva, 2015;Lopez, Kundu, & Ciravegna, 2009). Such a regional focus may be one of the typical characteristics of the accelerated expansion path followed by companies originating in the CEE countries.…”
Section: Discussionsupporting
confidence: 90%
“…This strategy implies that high-technology SMEs, including INVs, tend to survive by finding new global markets [12]. In addition to these findings, several studies [1,13] have reported a significant correlation between certain characteristics (e.g., global orientation) of the top management team, CEO, or founders and the rapid internationalisation process. Therefore, the CEOs' characteristics such as global orientation must be considered when investigating the internationalisation process.…”
Section: Introductionmentioning
confidence: 95%
“…This study aims to explore the role of the chief executive officers (CEOs)' global orientation ("the intention of penetrating international market" [1]) in determining internationalisation. It is particularly important for small-and medium-sized enterprises (SMEs) that aspire to sell their products at the global scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations